A study of relationship between SARS-CoV-2 antibodies levels and host factors among general population in Zakho City, Iraq - R Hussein, Nawfal; A Naqid, Ibrahim; A Jamal, Shakir; Balatay, Amer; Ibrahim, Nashwan; H Musa, Dildar; S M. Saleem, Zana (Journal of Contemporary Medical Sciences, 2022)
Objectives: The aim of this cross-sectional study is to evaluate the seroprevalence of total antibodies to SARS-CoV-2 and associated risk factors in Zakho City, Kurdistan Region of Iraq. Methods: This cross-sectional study was performed at Zako City, Northern, Iraq. Blood samples were collected from different districts of Zakho city between January and March 2021. Immunoassays were performed to detect the total antibodies against SARS-CoV-2, and the associations between several variables were investigated. Results: A total of 315 participants were agreed and enrolled in the study. The average age of the participants was 32.87±13.25 years. Among the participants, 214/315 (67.93%) were found to have antibodies against SARS-CoV-2. Among those who had positive antibodies, 169/214 (78.97%) were asymptomatic and 45/214 (21.03%) had a history of COVID-19 related symptoms. The most common symptom was fever (95.56%), followed by loss of smell (84.44%) and myalgia (80.0%). We found that antibody levels significantly associated with age (P=0.021). The presence of symptoms was significantly higher among subjects with a history of comorbidity diseases (P=0.038), and older people (P = 0.015). A significant association was found between antibody levels and the marital status (P=0.014), chronic diseases (P=0.001), presence (P=0.015) and duration of symptoms (P=0.028). Conclusion: A significant association between antibody levels to SARS-CoV-2 and age, chronic diseases, presence and duration of symptoms were found in this study. Seroprevalence studies of antibodies to SARS-CoV-2 among general population are of utmost importance to develop infection prevention programs in our society.